Regional innovation supporting agencies: international experience and lessons for Vietnam - Bui Ngoc Thu Ha; Tran Thanh Son (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
In the context of globalization and increasingly fierce economic competition, not only internationally but also domestically, many places around the world have identified innovation as the key to sustainable local development. Particularly, encouraging and supporting innovation at the local level has become a critical strategy to maximize the unique innovative potential of each region. Recognizing the importance of this, some areas in Europe have implemented various organizational models aimed at promoting and creating a favorable environment for unique local innovation activities. The study emphasizes the importance of building a diverse, flexible, and locally tailored support organization, as well as the necessity of promoting cross-sectoral collaboration to optimize the innovative potential in each region. This article investigates several exemplary organizations in three different regions of the world, to draw lessons for Vietnam. Code: 24052001